Experiências de si no limite da linguagem: o corpo como página - Vieira, Isabel Nunes (2011)
This paper aims to discuss the experience of writing as a literary form to reveal the erotic in the extreme situations, both with regard to the bodies and in relation to language. The procedure adopted takes the very thesis of this process as a living experiment. We tried to work and give expression to four scenes: the Supplicant, The Delicacy, The Book-body and a final scene that focuses previous experiences, The Delicacy and Calligraphy Bodies Subscribers